Molecular survey of coccidian infections of the side-blotched lizard Uta stansburiana on San Benito Oeste Island, Mexico - Quillfeldt, Petra; Romeike, Tanja; Masello, Juan F.; Reiner, Gerald; Willems, Hermann; Bedolla-Guzmán, Yuliana; Justus Liebig University Giessen (My University, 2018)
Blood parasites are found in many vertebrates, but the research on blood parasites of lizards is still at its onset. We analyzed blood samples from side-blotched lizards Uta stansburiana from San Benito Oeste Island, Mexico, to test for the presence of hemoparasites. We found a high prevalence (23 out of 27 samples) of a blood parasite of the genus Lankesterella (Coccidia, Eimeriorina, Lankesterellidae) according to phylogenetic analyses of the parasite 18S rRNA gene. Similar parasites (97-99% similarity) have recently been described for Uta stansburiana from California. The parasite 18S rRNA gene showed high variability, both within San Benito and compared to California. The next closest matches of the parasite DNA with 97-98% similarity included a range of different genera (Lankesterella, Schellackia, Eimeria, Isospora and Caryospora). A high uncertainty in the deeper branches of the phylogenetic trees, and many missing links in genetic network analysis, were in line with previous suggestions that the coccidians are an understudied group with large knowledge gaps in terms of their diversity and taxonomy. Further studies are needed to resolve the evolutionary relationships within the Eimeriorina.
Keywords: blood parasites; lizard; Lankesterella; coccidians; Eimeriorina; ddc:590